Kimono design : an introduction to textiles and patterns - Nitanai, Keiko, 1954- (Tuttle Publishing, 2017)
Kimono Design: An Introduction to Textiles and Patterns uses hundreds of photographs and a wealth of information on colors, fabrics and embellishments to paint a portrait of Japanese culture, art and thought. Lavish classical patterns, sweeping scenes, and the many motifs that have been woven, dyed, painted or embroidered into these textiles reveal a reflectiveness, a sense of humor, and an appreciation of exquisite beauty that is uniquely Japanese. Organized according to motifs traditionally associated with each season of the year, Kimono Design interprets the kimono's special language as expressed in depictions of: - Flowers and grasses - Birds and other animals - Symbols of power, luck and prestige - Land-and-seascapes - scenes from literature, history and daily life - scenes of travel and the Japanese concept of other lands - and many others Extensive notes on all the motifs demonstrate how the kimono reflects changing times and a sense of the timeless. Information on jewelry, hairpins and other accessories is scattered throughout to give a fuller sense of the Japanese art of dress. This is a volume that Japanophiles, historians, artists and designers will all cherish.